2020
DOI: 10.1002/jso.26140
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the initial phase of COVID‐19 pandemic on surgical oncology services at a tertiary care center in Eastern India

Abstract: Background The COVID‐19 pandemic has caused a global health emergency and affected the resources in both the public and private health sectors significantly. The present study aims to assess the impact of the pandemic on the services by the department in the first 3 months since the first COVID case in the region. Methods The study period was from 16 March to 15 June 2020. We queried the database for data on site of the tumor, diagnosis, stage, tumor board decisions and planning, surgical procedures, adjuvant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 6 publications
(4 reference statements)
0
11
0
Order By: Relevance
“…Several tertiary level academic oncology centres from India have reported their experiences of cancer surgery during the pandemic 13‐19 . India's largest oncology centre was reported to have a decrease in operated cases by a third 20 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several tertiary level academic oncology centres from India have reported their experiences of cancer surgery during the pandemic 13‐19 . India's largest oncology centre was reported to have a decrease in operated cases by a third 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Shrikhande et al 13 reported outcomes in a large cohort of 494 patients from the same centre albeit performed over a smaller duration of 2 months with a similar incidence of postoperative complications as the present study. In the cohorts reported by Sultania et al 14 and Pai et al, 17 56 procedures and 184 major procedures were done, respectively. The incidence of postoperative complications was again higher than our present study, and one and three cases of mortality were reported, respectively 14,17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With this fixed protocol, not even a single patient had turned covid positive (in our department) in the postoperative period, when other departments of the hospital witnessed a number of patients positive for COVID‐19. Despite the state of Odisha, witnessing a surge of COVID‐19 cases in the month August and September, we never discontinued our surgical services (although, operations were reduced in number) at any phase of the pandemic 3 …”
mentioning
confidence: 99%
“…In the period between April 1 and November 15, 2020, 146 admissions were made and 95 elective cancer surgeries were performed. Early‐stage patients, patients receiving neoadjuvant therapy and palliative surgery were prioritized 3 . In our department, all out‐patients were screened with a set of questions about respiratory symptoms, travel history and exposure.…”
mentioning
confidence: 99%